Exercise interventions for weight management during pregnancy and up to 1 year postpartum among normal weight women and women with overweight and obesity: An updated systematic review - Stephanie J. Hanley; Elise Sibbick; Ian Varley; Craig Sale; Kirsty J. Elliott‐Sale (Wiley, 2022)
Abstract Background Given the increased occurrence of pre‐gravid obesity in recent years, and the implications of maternal obesity for maternal and offspring health, it is evident that there is a continued need to investigate antenatal and postnatal weight management strategies and to provide evidence‐based advice for exercise‐based interventions. Given the small number of studies (n = 5) included in an original systematic review by our group in 2015, it was important to add to the dataset by assessing data published since 2015, in order to provide a more in‐depth view of current knowledge. Objective To provide an updated systematic review on studies employing exercise interventions for weight management in pregnant and postpartum women. Methods A systematic review of randomised controlled trials evaluating the effects of an exercise intervention on gestational weight gain and postpartum weight management in normal weight women, and women with overweight and obesity was conducted. PubMed, Scopus, Central Register of Controlled Trials and Web of Science were searched for studies published between September 2013 and June 2021. No restrictions were set on type, intensity, duration, or frequency of exercise intervention. Only studies that targeted body weight or mass as a primary outcome were included. Results Thirteen studies were included in this review: 11 during and two following pregnancy. Exercise significantly reduced gestational weight gain in five of the pregnancy studies and induced significant weight loss in one of the postpartum studies. Across studies, there were large disparities in exercise modality, frequency, and duration, although moderate intensity exercise was consistently employed. Conclusions Some studies showed positive effects of exercise on weight management during and following pregnancy. While there is still no consensus on effective exercise intervention approaches, it is crucial that physical activity, of any safe form, is recommended to encourage healthy weight management during this time.